2021
DOI: 10.3390/membranes11050352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of F16-Betulin Conjugate on Mitochondrial Membranes and Its Role in Cell Death Initiation

Abstract: This work demonstrates the effects of a newly synthesized conjugate of the plant triterpenoid betulin and the penetrating cation F16 used for mitochondrial targeting. The resulting F16-betulin conjugate revealed a mitochondria-targeted effect, decreasing the mitochondrial potential and inducing superoxide overproduction in rat thymocytes in vitro. It has been suggested that this may cause the cytotoxic effect of the conjugate, which significantly exceeds the effectiveness of its precursors, betulin and F16. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
(61 reference statements)
0
22
0
Order By: Relevance
“…Fluorescent derivatives 4 and 6 colocalized with endoplasmic reticulum and mitochondria, which is in agreement with previous studies showing interaction with the processes and proteins localized in these organelles [ 55 , 56 ]. Uncoupling of the mitochondrial respiration, followed by radical burst and mitochondrial membrane disruption, is one of the well-described effects of betulin and betulinic acid [ 57 , 58 , 59 , 60 ]. Thus, we believe that reliable tools to study the derivatives of BA on living cells were established.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent derivatives 4 and 6 colocalized with endoplasmic reticulum and mitochondria, which is in agreement with previous studies showing interaction with the processes and proteins localized in these organelles [ 55 , 56 ]. Uncoupling of the mitochondrial respiration, followed by radical burst and mitochondrial membrane disruption, is one of the well-described effects of betulin and betulinic acid [ 57 , 58 , 59 , 60 ]. Thus, we believe that reliable tools to study the derivatives of BA on living cells were established.…”
Section: Discussionmentioning
confidence: 99%
“…The combinations of the F16 cation with the molecules of betulin or betulinic acid exhibiting anticancer activity show a significantly enhanced anti-tumor effect. These conjugates target the mitochondria by inducing an overproduction of ROS and a permeabilization of organelle membranes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary sources of ROS in cells is the mitochondrial respiratory chain. Dubinin et al [ 17 , 27 ] showed that betulin and its derivatives affected mitochondrial membranes and inhibited mitochondrial respiratory chain complexes, which is accompanied by an increased production of ROS. The authors also note that this may be the cause of the cytotoxicity of these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Although detailed information on how DLC conjugates mediate mitochondria-targeted cytotoxic effects that are highly cancer-specific is still missing, a couple of mechanisms have been suggested. Depending on the particular DLC compound and its conjugate, these include a surface-active effect on mitochondrial membranes causing organelle aggregation, a dose-dependent decrease in mitochondrial transmembrane potential, suppression of oxidative phosphorylation, an increase in H 2 O 2 generation, induction of apoptosis in an ROS-mediated manner, suppression of the STAT3 activation pathway, autophagy, cell cycle arrest, inhibition of mtDNA replication, inhibition of the activity of complexes of the respiratory chain, influence on the balance between pro- and anti-apoptotic proteins and others (for more details, see [ 320 , 321 ]).…”
Section: Therapeutic Potentialmentioning
confidence: 99%